Pengaruh Variasi Waktu Ekstraksi terhadap Rendemen dan Total Kurkuminoid Ekstrak Etanol 96% Temu Giring (Curcuma heyneana) menggunakan Metode Microwave-Assisted Extraction - Mutia Nur Oktavia; Hanif Rifqi Prasetyawan (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
This study aimed to evaluate the effect of extraction time variations on the yield and total curcuminoids of 96% ethanol extract of temu giring (Curcuma heyneana) using the Microwave-Assisted Extraction (MAE) method. Extraction was performed at 20, 60, 120, and 150 seconds using an 800-watt microwave with a 1:10 (w/v) solvent ratio. Yield was calculated based on total solids, while total curcuminoids were quantified using UV-Vis spectrophotometry at 469 nm. The results showed an increase in yield from 2.40% (20 s) to 7.52% (150 s) and total curcuminoids from 2.3962 µg/mL to 5.9593 µg/mL. Statistical analysis indicated a significant difference between treatments (****p < 0, 0001). Based on the tested time range 150-second exteaction time was identified as optimum, maximizing cell rupture and solvent diffusion without compromising thermal stability of curcuminoids. Thus, extraction time plays a key role in optimizing green extraction of temu giring.